2016
DOI: 10.4081/aiua.2015.4.295
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of local steroid injection after internal urethrotomy to avoid recurrence

Abstract: The use of local steroids with IU seems to decrease the high stricture recurrence rate following IU. When local steroids were administered with complementary intention, the disease control outcomes are encouraging. Further robust comparative effectiveness studies are now required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…In patients administered with simultaneous mitomycinc, promising results were demonstrated in the early period, and 75 % of the patients did not require additional intervention for 2 years (7). In another randomized study, methylprednisolone was used and a 95% success rate was observed in the 18-month follow-up (13). In their study, Kumar et al determined a success rate of 95.8% in a 12-month follow-up in laser urethrotomy in strictures less than 1 cm along with quadruplet injection (mitomycin-c, hyaluronidase, triamcinolone, n-acetylcysteine) (14).…”
Section: Discussionmentioning
confidence: 98%
“…In patients administered with simultaneous mitomycinc, promising results were demonstrated in the early period, and 75 % of the patients did not require additional intervention for 2 years (7). In another randomized study, methylprednisolone was used and a 95% success rate was observed in the 18-month follow-up (13). In their study, Kumar et al determined a success rate of 95.8% in a 12-month follow-up in laser urethrotomy in strictures less than 1 cm along with quadruplet injection (mitomycin-c, hyaluronidase, triamcinolone, n-acetylcysteine) (14).…”
Section: Discussionmentioning
confidence: 98%
“…18 The numbers were too small, however, to justify post hoc subgroup analysis in the OPEN trial. Other investigators have trialled a number of drugs injected into the strictures area at the time of urethrotomy, including steroids 92 and mitomycin C, 93 but there is no robust evidence of benefit. 94 Another approach is to maintain luminal patency using an internal stent, but again there is no robust evidence of effectiveness.…”
Section: Statement and Interpretation Of Resultsmentioning
confidence: 99%
“…In a very recent study conducted in 2018, patients who received 10 mg tamoxifen daily for six months after internal urethrotomy were compared with the control group, and tamoxifen was shown to significantly reduce re-fibrosis and stricture development. Again in 2016, in a study with 83 patients, Yıldırım et al 20 showed that recurrence is significantly lower in patients who received a local urethral steroid injection compared with a control. Sinanoglu et al 21 conducted a similar study with 84 patients and used colchicine as an anti-inflammatory agent, and the recurrence in this group was significantly lower.…”
Section: Discussionmentioning
confidence: 99%